Growth Performance of Mono Sex and Mixed Sex Climbing Perch (Anabas testudineus) - Helmizuryani Helmizuryani; Boby Muslimin (Journal Omni-Akuatika, 2016)
Many factors influence fish growth like rearing by sex. This study aims to determine the growth of theClimbing perch of the different sexes. This research was conducted at hatchery business unit at MulyaPlaju, from May to July 2015. Fry spawning fish came from the wet Laboratory Faculty of Agriculture,University of Muhammadiyah Palembang. They were maintained separately between the male and thefemale and the gender-mix between male and female, reared in nets with a density of 30 individualseach net; each treatment was repeated three times. During the research, fry feed used artificial feedwith 30% protein compotition.  The results showed that there was growth of female was faster than ofmale and of mixed sex. The growth of fish was 1,40 cm and weight of 4.56 gr, while survival rate ofthem was 100%. Keywords : growth, Anabas testudineus, mixed sex,  mono sex